EXPLORING PROFESSIONALISM: CHARACTERISTICS AND SELF-CONCEPT OF IMPLEMENTING NURSES - Sulistyowati, Arlina Dhian; Nurhidayati, Istianna; Setianingsih, Setianingsih; Kusumaningrum, Puput Risti (Universitas Airlangga, 2025)
Introduction: To enhance the delivery and quality of nursing care, which in turn affects nurse satisfaction, a professional self-concept among nurses is required. Various factors, including the nature of nursing, impact this self-concept. In this study, the professional self-concept of implementing nurses at Pandan Arang Hospital in Boyolali was compared with several nurse characteristics. Methods: The research methodology employed a cross-sectional descriptive correlational design. Seventy-two nurses in inpatient wards served as the research sample, selected using a total sampling approach. The questionnaire on nurses' professional self-concept was taken from Angel, Craven, and Denson, which was adopted by Juanamasta, covering four aspects: care, knowledge, staff relations, and leadership. As part of the data-gathering method, a questionnaire was utilized. Results: According to the research findings, among the nurses at Pandan Arang Boyolali Hospital, the majority (51.1%) had a positive professional self-concept. Furthermore, there was no significant relationship between age, gender, employment status, or length of work and nurses' professional self-concept, as indicated by a p-value > 0.05. However, a significant relationship was found between marital status and nurses' professional self-concept, as indicated by a p-value < 0.05. Conculsions: The results of this study suggest that age, gender, employment status, and length of employment are not significantly related to nurses’ professional self-concept. However, a significant relationship was observed between marital status and nurses' professional self-concept.